jawquin
contestada

What is the product of 2p + q and -39 - 6p + 1?
0 -12p2 - 6pq – 4p - 32 + 1
O-12p2- 12pq + 2p – 392 +9
- gp² q² + 12pq - 2p + 9
12p2 + 12pq +2p + 302 + 9

What is the product of 2p q and 39 6p 1 0 12p2 6pq 4p 32 1 O12p2 12pq 2p 392 9 gp q 12pq 2p 9 12p2 12pq 2p 302 9 class=

Respuesta :

Answer:

Option (2)

Step-by-step explanation:

In this question we have to find the multiplication of the two expressions.

(2p + q)(-3q - 6p + 1)

= 2p(-3q - 6p + 1) + q(-3q - 6p + 1) [By distributive property]

= -6pq - 12p²+ 2p - 3q² - 6pq + q

= -12p² - (6pq + 6pq) - 3q² + 2p + q

= -12p² - 12pq + 2p - 3q² + q

Therefore, Option (2) will be the correct option.